基于场景中的运动水平优化捕获场景的图像帧序列中的图像帧的曝光的相机和方法 (2017)
本发明涉及基于场景中的运动水平优化捕获场景的图像帧序列中的图像帧的曝光的相机和方法。这通过下面的步骤来实现：根据来自多个图像传感器帧的图像数据，确定场景的包括不同运动水平的区域；确定上述图像帧的图像帧区域，其中图像帧区域对应于场景的至少个区域；以及通过利用来自多个图像传感器帧的图像数据产生每个图像帧区域，通过对每个图像帧区域的区域特定曝光时间进行模拟，优化图像帧的曝光，其中用于产生特定图像帧区域的图像传感器帧的数量是基于场景的至少个对应区域中的运动水平。 The present invention relates to a method and camera for optimizing the exposure of an image frame in a sequence of image frames capturing a scene based on level of motion in the scene. This is made by: determining, based on image data from a plurality of image sensor frames, regions of the scene comprising different level of motion; determining image frame regions for said image frame, wherein an image frame region corresponds to at least one region of the scene; and optimizing the exposure of the image frame by emulating a region specific exposure time for each image frame region by producing each image frame region using image data from a number of image sensor frames, wherein the number of image sensor frames used to produce a specific image frame region is based on the level of